Rules of Origin: Evolving Best Practices for RTAs/FTAs - Erlinda M. Medalla; Dorothea C. Lazaro (Philippine Institute for Development Studies (PIDS), 2006)
The paper aims to add to the understanding of the issues and suggests a framework to move toward the use of best practice in ROOs. Rules of origin (ROO), originally designed as uncontroversial and neutral devise for authentication and statistical purposes, have evolved over time to accommodate different purposes which come about with new technologies and other developments, across different trade regimes. ROO is becoming a tool in implementing discriminatory trade policies and trade policy instrument per se. ROO has become a critical and to some extent, a dragging point in the negotiation process of recent trade agreements. The growing relevance of ROO in trade negotiations cannot be overemphasized. The paper begins with the definition that has been adopted and traces the developments in the use of ROOs. It looks at ROOs within the context of multilateral rules of origin and the preferential ROO in Regional or Bilateral FTAs. Different types of ROO with some illustration from existing RTA are also presented. The paper also focuses on some recurring ROO issues, and presents some suggestions for a framework for ROO best practices which is characterized by transparency, predictability, neutrality, and non-discrimination, and with the added dimension of being development-friendly.
Keywords: 330; World Trade Organization; regional integration; rules of origin; free trade agreements (FTAs); Außenwirtschaftspolitik; Protektionismus; Herkunftsbezeichnung; Freihandelszone; WTO-Recht; Regionale Wirtschaftsintegration